A dual-role of Gu-4 in suppressing HMGB1 secretion and blocking HMGB1 pro-inflammatory activity during inflammation. - Huiting Zhou; Xuemei Ji; Yun Wu; Ju Xuan; Zhilin Qi; Lei Shen; Lei Lan; Qing Li; Zhimin Yin; Zhongjun Li; Zhihui Zhao (PLoS ONE, 2014)
BACKGROUND: High mobility group box 1(HMGB1) was first recognized as a nuclear protein that increased the chromatin remodeling and regulates transcription of many genes. In recent years, HMGB1 has been identified as a critical "late" pro-inflammatory mediator due to its unique secretion pattern and lethal effects in sepsis. Therefore, preventing the active release and inhibiting the pro-inflammatory activity of HMGB1 become promising strategies for the treatment of sepsis. Here, we reported the therapeutic effects of Gu-4, a lactosyl derivative, on sepsis and the underlying molecular mechanisms. METHODOLOGY/PRINCIPAL FINDINGS: In an experimental rat model of sepsis caused by cecal ligation and puncture (CLP), Gu-4 administration prominently attenuated lung injury and improved the survival of the septic animals, which was positively correlated with the decrease of the serum HMGB1 level. Using RAW264.7 macrophage cell line, we further showed that Gu-4 significantly suppressed the lipopolysaccharide (LPS)-induced release and cytoplasmic translocation of HMGB1. Moreover, Gu-4 not only dose-dependently attenuated recombinant human (rhHMGB1)-induced production of TNF-α, IL-6, and IL-1β in THP-1 cells, but also greatly inhibited the adhesion of rhHMGB1-challenged THP-1 cells to HUVECs. Analyses of flow cytometry demonstrated that Gu-4 could effectively reduce the activation of CD11b elicited by rhHMGB1. Western blot analyses revealed that Gu-4 treatment could partially block the rhHMGB1-induced activation of ERK and NF-κB signalings. Meanwhile, CD11b knockdown also obviously attenuated the rhHMGB1-induced phosphorylations of ERK and IKKα/β. CONCLUSIONS/SIGNIFICANCE: Taken together, our results suggest that Gu-4 possesses a therapeutic potential in the treatment of sepsis probably via inhibiting the LPS-induced release of HMGB1 from macrophages and via suppressing the pro-inflammatory activity of HMGB1.